The Mormon Jesus: A Biography, by John G. Turner. (12th July 2018) - Gullotta, Daniel
Abstract : The Mormon Jesus: A Biography, by John G. Turner. Belknap Press of Harvard University Press, 2016. 368pp., 27 halftones. Hb. 29.95 / £21.95 / €27.00. ISBN-13: 9780674737433.